THE EFFECTIVENESS OF USING IMAGE MEDIA AND REALIA MEDIA ON THE LISTENING ABILITY OF CHILDREEN AGED 4-5 YEARS - Indah Patih Kurniawati Putri Hardini; Warananingtyas Palupi; Adriani Rahma Pudyaningtyas (Early Childhood Education and Development Journal, 2020)
The aim of this research is to find the effectiveness of pictures and realia usage towards the listening capability of children at 4-to-5 year old. This research uses comparative method to compare two groups that is pictures and realia as the instructional media. Meanwhile, the variable on this research is the listening capability of the children. The population of this research is all students of Gugus 9 Bugenvil Kindergarten School Surakarta grade A. The chosen samples are Berita Hidup Kindergarten School, Indriyasana Kindergarten School, Paramayoga Kindergarten School, and Animah Kindergarten School. They are chosen by using the cluster random sampling method. The data is collected through performances, interview, and documentation. In analyzing the data, the researcher uses One Way ANOVA. The result of this research shows that there is no difference between the listening capabilities of children at 4-to-5 year old based on the pictures and realia usage. The use of instructional media either pictures or realia must considers the number of the children in a class and also the size of the instructional media itself, therefore it can be effective.